Implications of Spaceborne High-Resolution Solar Spectral Irradiance Observation for the Assessment of Surface Solar Energy in China - Chenxi Kong; Xianwen Jing; Xiaorui Niu; Jing Jing (Energies)
Accurate solar spectral irradiance (SSI) input is key to modelling climate systems. Traditional SSI data used in the climate modelling community are based on solar model calculations joined by limited observations. Recent advances in spaceborne high-resolution solar spectrum observations, such as the National Administration for Space and Aeronautics (NASA)’s Total and Spectral Solar Irradiance Sensor (TSIS), have provided more accurate and reliable SSI alternatives. Here, we investigate the differences between the observed and the model-based SSIs, and how these affect the modelled downward surface shortwave radiation (DSSR) over different regions of China. Special interest is dedicated to the implications for solar power estimation from solar farms. We conduct idealized calculations using the RRTMG_SW radiative transfer model, with the traditional China Meteorological Administration standard solar spectrum (CMA_STD) and the observed TSIS-1 Hybrid Solar Reference Spectrum (TSIS-1_HSRS). Results show that the CMA_STD SSI yields 4.45 Wm−2 less energy than the TSIS-1_HSRS, and systematically overestimate energy in the infrared bands and underestimate that in the visible bands. These discrepancies result in an annual regional mean DSSR underestimation of ~0.44 Wm−2, with localized underestimation for a particular month exceeding 2 Wm−2. The estimated solar power productions with the two SSIs differ by 0.25~0.32% and 0.36~0.52% of the total power production capacity for fixed-angle and solar tracking panels, respectively. These findings suggest that long-term and high-resolution spaceborne SSI observations are crucial to improve surface climate modelling, especially on local scales, and to service climate change mitigations.